Acute Toxicity of Monocrotophos on Histological Alterations in the Anomuran Crab, Emerita asiatica (H. Milne Edwards, 1837) - Sivakumar, J.; Bhuvaneswari, S.; Venu, S.; Jemima Ezhilarasi, J.; Shanmugasundaram, C.; Sankarganesh, P. (Asian Journal of Engineering and Applied Technology, 2022)
This study characterized the acute toxicity of Monocrotophos on histological alterations in the different organs like gills, Hepatopancreas and ovary of Anomuran Crab, Emerita asiatica. Though Emerita asiatica is not a commercially viable crab, but it plays a vital role in the coastal environment to maintain a stable marine ecosystem. Several steps and precautions measures should be taken to consume these members of the marine food chain to have aunwavering ecosystem and also to protect this species from extinction. Thus, it can be concluded that the use of Monocrotophos which has been legally banned in India is justified. It has been proved by several workers and has been conformed in present investigation that use of this organophosphate causes serious damage to the vital organ of sand crabs gill, hepatopancreas and ovary. The utilization of Monocrotophos should be minimized in the agricultural field area near to the coastal ecosystem.